The Influence of Communication Effectiveness, Service Quality and trust on Commitment Connectedness to customers - Fakhrudin Fakhrudin; Shaiffurokhman Mahfudz; Muhammad Isa Mustafa (Journal of Business Innovation and Research, 2022)
The purpose of the study is to This will examine the strong influence of communication effectiveness, functional quality and technical quality on commitment to connectedness with trust as a mediating variable, the quantitative method used in this study is path analysis is used to  determine the effect of communication effectiveness, technical quality, functional quality and trust on connectedness commitment. There are 4 stages of regression; The connectedness commitment, The confidence, The functional quality And The technical quality variable. The conclusions obtained from this research are The regression coefficient which shows the relationship between communication effectiveness and connectedness commitment, The effectiveness of communication does not affect trust directly, but through the perception of technical quality and functional quality, Technical quality is also known to influence commitment to connectedness through trust, quality and trust  This shows that the perception of functional quality affects customer connectedness commitment more than technical quality and Service quality is a variable that affects trust, while effective communication will create a higher perception of service quality in the eyes of customers.